2020
DOI: 10.3349/ymj.2020.61.8.660
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR-146b-5p Ameliorates Neonatal Hypoxic Ischemic Encephalopathy by Inhibiting IRAK1/TRAF6/TAK1/NF-αB Signaling

Abstract: Purpose: Neonatal hypoxic ischemic encephalopathy (HIE) is an essential factor underlying neonatal death and disability. This study sought to explore the role of miR-146b-5p in regulating neonatal HIE. Materials and Methods: In vitro and in vivo HIE models were established in PC12 cells and 10-day neonatal Sprague Dawley rats, respectively. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) was used to assess miR-146b-5p expression and inflammatory factors [interleukin (IL)-6 and tumor necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…SOD is an active substance derived from living organisms, which can eliminate harmful substances produced during metabolism [ 25 ]. It is confirmed that the SOD level in neonates with HIE is significantly lower than that of normal neonates [ 26 ]. In this study, the SOD level increased in all three groups after treatment, with the most significant increase in the combination group, suggesting that the combined treatment for HIE can more effectively increase the SOD level in neonates.…”
Section: Discussionmentioning
confidence: 88%
“…SOD is an active substance derived from living organisms, which can eliminate harmful substances produced during metabolism [ 25 ]. It is confirmed that the SOD level in neonates with HIE is significantly lower than that of normal neonates [ 26 ]. In this study, the SOD level increased in all three groups after treatment, with the most significant increase in the combination group, suggesting that the combined treatment for HIE can more effectively increase the SOD level in neonates.…”
Section: Discussionmentioning
confidence: 88%
“…Hypoxemia is a common cause of acute neuron injury. In the injured neuron area, massive inflammation and a large amount of proinflammatory cytokines are expressed, due to hypoxemia-induced oxidative stress and cell damage [ 10 , 11 ]. Treatment with anti-inflammatory reagents and neurotrophic factors becomes essential in the prevention and treatment of acute neuron injury in vivo [ 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, neonatal hypoxic ischemic encephalopathy is an essential factor underlying neonatal death and disability. In the neonatal hypoxic ischemic encephalopathy models established in 10-day-neonatal Sprague Dawley rats, TAK1/NF-κB signaling was significant increased by oxidative stress and inflammatory responses [ 39 ]. TAK1 was found to be critically involved in sepsis-induced multiple organ dysfunction [ 40 ].…”
Section: Discussionmentioning
confidence: 99%